Implementasi Six Sigma untuk Perbaikan Kualitas Produk Kiwi Paste Berdasarkan Keluhan Pelanggan - Nelfiyanti, Nelfiyanti; Rani, Annisa Mulia; Fauzi, Achmad (Universitas Serang Raya, 2018)
PT. LF Beauty Manufacturing Indonesia is a Hong Kong-based Li & Fung group of companies engaged in manufacturing services. The Company has 4 regular customers, namely: PT JHHP, PT.Diversey, PT.Topindo and PT.Wavin. During 2015 the company got 12 defect complaints which 8 complaints came from PT. JHHP. This study aims to determine the cause of disability complaints of PT JHHP, provide improvements to existing problems so that it does not occur in the future and as a measure of company productivity to improve production quality. This research method uses Six Sigma with DMAIC stages (Define Measure, Analyze, Improvement, Control). The object of research is the production data of August 2015 in accordance with customer complaints data. The result of analysis of JHPP customer's complaint obtained the biggest defect of kiwi paste product according to the diagram is finish good leak. Factors affecting the defect complaints of the finish good leaked kiwi paste product is the operator often do autocapper engine wind adjusment, unavailability of space thermometer tool in the warehouse area and dry production area, unavailability of wind pressure gauge used to determine the number of bars used in the asemble process and the temperature of the storage area space exceed the standard set. Defect value decreased, before implementation of 3.497 DPMO with sigma level 4.20 to 568 DPMO with 4.75 sigma level